Identifying the location of locoregional recurrences after definitive radiotherapy for head and neck cancer using metabolic parameters of baseline and mid‐treatment 18F‐FDG‐PET scans. Issue 1 (27th October 2022) - Aren, Ewa; Trada, Yuvnik; Lee, Mark; Deshpande, Shrikant; Jameson, Michael G; Johnston, Meredith; Berry, Megan; Estall, Vanessa; Fowler, Allan
Abstract: Introduction: Tumour recurrences after treatment of head and neck squamous cell carcinoma (HNSCC) are more likely to originate from regions of high‐baseline FDG‐PET uptake. Mid‐treatment functional imaging can potentially predict for higher risk of tumour recurrence. The aim of this study is to correlate the location of locoregional tumour recurrence with baseline FDG‐PET metabolic volumes and mid‐treatment FDG‐PET metabolic volumes in patients with HNSCC following definitive radiotherapy. Methods: A total of 23 patients with 26 local and/or regional recurrences underwent baseline (W0‐PET) and mid‐treatment (W3‐PET) 18F‐FDG PET scans as part of their radiotherapy. FDG‐PET‐based metabolic volumes (MTV20%, MTV40%, MTV60%, MTV80%, SUV2.5, SUVpeak and PET_EDGE) were delineated onto the FDG‐PET scans. The recurrence nidus was identified on FDG‐PET at the time of recurrence (REC‐PET). DIR‐based fusion was performed for REC‐PET to W0‐PET, and REC‐PET to W3‐PET. The location of the recurrence nidus was correlated with the FDG‐PET volumes. Further analysis included a comparison of the recurrence density to FDG‐PET metabolic volumes. Results: Most recurrences occurred within the MTV20%, MTV40% and SUV 2.5 volumes. Sixty‐nine per cent of recurrences (18 of 26) occurred within both the W0 MTV40% and W3 MTV40% volumes. A higher recurrence density was seen for iso‐SUV contours closer to the maximum SUV for both W0 and W3. For a number of the FDG‐PET volumes, including MTV20%, MTV40% and SUV2.5, the recurrence density was improved for W3 compared to W0, however, this improvement was small in magnitude. The average volume of MTV40% contours was considerably smaller than MTV20% and SUV2.5 contours. Conclusion: The metabolic parameters of SUV2.5, MTV20% and MTV40% delineated on the baseline and mid‐treatment FDG‐PET scans encompassed the majority of recurrences. The MTV40% is significantly smaller, hence, we prefer this volume for future dose escalation studies.